Communication Strategies of PKBM in Implementing the PKW Graphic Design Program - Yuchi Syahriani Putri; Ernita Syarif; Asmawi (Walidem Institute and Publishing, 2026)
Objective: This study examines the communication strategies employed by Community Learning Activity Centers (PKBM) in implementing the Entrepreneurship Education Program (PKW), focusing on institutional communication, participant engagement, and program sustainability. The study highlights how strategic communication contributes to program effectiveness and community empowerment. Theoretical Framework: The analysis is grounded in communication strategy theory, development communication, and institutional communication, emphasizing message planning, stakeholder involvement, and communicative action in community-based education programs. Literature Review: The review discusses theories of communication strategy, non-formal education studies, PKBM institutional roles, community empowerment, and previous research on PKW implementation in Indonesia. Methods: Using a qualitative case study at PKBM Suka Maju Sejahtera, Padang City, data were collected through in-depth interviews, observation, FGDs, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, supported by NVivo 12 Plus for coding, word frequency, and hierarchy analysis. A SWOT analysis was then applied to synthesize internal and external factors and formulate strategic communication alternatives. Results: The findings indicate that PKBM’s communication strategy plays a critical role in aligning program objectives with community needs, strengthening participant motivation, and ensuring program continuity. Interpersonal communication, participatory approaches, and institutional credibility emerged as key factors in successful PKW implementation. Implication: This study underscores the importance of structured and context-sensitive communication strategies in non-formal education institutions to enhance program effectiveness and community impact. Novelty: This research contributes by positioning institutional communication of PKBM as a strategic element in PKW implementation, offering a communication-based model for strengthening entrepreneurship education in community learning settings.